A randomized controlled trial of the effects of working memory training in methadone maintenance patients. (1st November 2015) - Rass, Olga; Schacht, Rebecca L.; Buckheit, Katherine; Johnson, Matthew W.; Strain, Eric C.; Mintzer, Miriam Z.
Highlights: Methadone patients improved on working memory tasks similar to the training program. Working memory training did not produce near or far transfer in methadone patients. Working memory training did not affect delay discounting in methadone patients. Abstract: Objective: Working memory impairment in individuals with chronic opioid dependence can play a major role in cognitive and treatment outcomes. Cognitive training targeting working memory shows promise for improved function in substance use disorders. To date, cognitive training has not been incorporated as an adjunctive treatment for opioid dependence. Methods: Methadone maintenance patients were randomly assigned to experimental ( n  = 28) or active control ( n  = 28) 25-session computerized training and run in parallel. Cognitive and drug use outcomes were assessed before and after training. Results: Participants in the experimental condition showed performance improvements on two of four working memory measures, and both groups improved on a third measure of working memory performance. Less frequent drug use was found in the experimental group than in the control group post-training. In contrast to previous findings with stimulant users, no significant effect of working memory training on delay discounting was found using either hypothetical or real rewards. There were no group differences on working memory outcome measures that were dissimilar from the training tasks, suggesting that another mechanism (e.g., increased distress tolerance) may have driven drug use results. Conclusions: Working memory training improves performance on some measures of working memory in methadone maintenance patients, and may impact drug use outcomes. Working memory training shows promise in patients with substance use disorders; however, further research is needed to understand the mechanisms through which performance is improved and drug use outcomes are impacted.